대형구조물의 파괴강도 특성 평가기술에 관한 연구 - 한문식(Moon Sik Han) (大韓造船學會 論文集, 1993)
One of the most important design procedures for large sized structures is the evaluation of fracture strength against fatigue and brittle fractures threatening to occur in their steel members. In this paper, the safety assessment based upon the knowledge about the fracturing characteristics of such ship structures was discussed, which can be estimated from such phenomena as fatigue crack propagation and brittle fractures, as obtained by employing fracture mechanics at the basic design stage. Model tests with a partial structure specimen of full size was carried out to authenticate a question as to whether or not the fracturing characteristics of such sophisticated structures could be estimated with precision from ordinary scale specimen tests, It was shown that the behviour of fatigue crack growth of large sized structures in this study could be predicted from the results of ordinary scale specimen test. 대형구조물에서 발생되는 피로 및 취성파괴에 대한 강도의 특성 평가는 대형구조물의 설계에서 중요한 검토 사항중에 하나이다. 본 논문에서는 대형선체 및 해양구조물과 같은 대형구조물의 기본 설계단계에서 파괴역학을 이용하여 피로균열 진전과 취성파괴 발생 및 정지등에 대한 구조물의 파괴 강도 특성을 파악하고 이것을 기초로 이에 대한 안전성평가를 검토하였다. 소형시험 결과에서 선체구조의 상갑판 전단부와 같은 복잡한 구조물의 피로파괴 강도특성을 정도가 높고 또한 간편하게 추정할 수 있는가에 대하여, 실물크기 부분구조 모델시험을 실시하여 이를 비교 검토하였다. 본 연구대상에서는 소형시험결과를 기초로해서 대형구조물의 피로균열전파거동을 예측할 수 있음을 보였다.